2019
DOI: 10.1093/monist/onz022
|View full text |Cite
|
Sign up to set email alerts
|

Naturalness and Emergence

Abstract: I develop an account of naturalness (that is, approximately: lack of extreme fine-tuning) in physics which demonstrates that naturalness assumptions are not restricted to narrow cases in high-energy physics but are a ubiquitous part of how interlevel relations are derived in physics. After exploring how and to what extent we might justify such assumptions on methodological grounds or through appeal to speculative future physics, I consider the apparent failure of naturalness in cosmology and in the Standard Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…When they hold, they can legitimately be exploited in inferences. Assumptions concerning the absence of various sorts of special tuning are common in many areas of science and, as argued in Wallace (2019), it is not clear that science can proceed without reliance on some of them. Although I don't have space to argue this in detail, a great deal of causal reasoning in science including physics seems to rest on assumptions about the absence of special tuning of various kinds-a point that is suggested both by JZ's and KZ's discussions as well as that of Porter Williams, to which I now turn.…”
Section: Response To Jiji Zhang and Kun Zhangmentioning
confidence: 99%
“…When they hold, they can legitimately be exploited in inferences. Assumptions concerning the absence of various sorts of special tuning are common in many areas of science and, as argued in Wallace (2019), it is not clear that science can proceed without reliance on some of them. Although I don't have space to argue this in detail, a great deal of causal reasoning in science including physics seems to rest on assumptions about the absence of special tuning of various kinds-a point that is suggested both by JZ's and KZ's discussions as well as that of Porter Williams, to which I now turn.…”
Section: Response To Jiji Zhang and Kun Zhangmentioning
confidence: 99%
“…for anthropic considerations see (Polchinski 2006); see also (Wallace 2019b) and references therein.…”
Section: The Cosmological Constant Problemmentioning
confidence: 99%
“…Indeed, this approach has the interesting consequence of dissolving the distinction between initial conditions and parameter values. Wallace has observed that the physical content of a theory has three aspects: the qualitative form of its dynamical equations (in which the coefficients are unspecified parameters); the actual, numerical values of the parameters (expressed as dimensionless ratios); and the initial conditions [45]. As Wallace notes, it is common to consider that the parameter values are 'lawlike' while the initial conditions are merely 'contingent' -that is, parameters and initial conditions are usually thought to have importantly different modal status.…”
Section: Solutionsmentioning
confidence: 99%